Expression and distribution of aquaporin of collecting duct are regulated by vasopressin V2 receptor in rat kidney. - Hayashi, M (1994)
To examine whether expression and distribution of aquaporin of collecting duct (AQP-CD) are regulated by vasopressin V2 receptor (V2R), we performed immunohistochemical studies with specific antibody against AQP-CD. Normal Wistar rats were divided into four groups and treated for 3 d; control, dehydration, vasopressin V1 receptor (V1R) antagonist (OPC-21268 120 mg/kg), V2R antagonist (OPC-31260 30 mg/kg). At time of death, urine osmolality (Uosm) in the dehydration group (1884 +/- 245 mOsm/kg) was significantly higher than that in the control (938 +/- 91). In the V2R antagonist group, Uosm was significantly decreased to 249 +/- 29, whereas V1R antagonist showed no effect on Uosm. In the control and V1R antagonist groups, immunofluorescence studies showed the AQP-CD staining of both apical membrane and subapical cytoplasm of CD cells of the cortex and the inner medulla. Dehydration increased the immunostaining of both apical membrane and subapical cytoplasm of CD cells of the inner medulla, and the degree of increase was dominant in apical membrane. In the V2R antagonist group, only faint staining of apical membrane and weak labeling of cytoplasm of CD cells of the inner medulla were observed. These changes in the localization and protein amount of AQP-CD by dehydration and V2R antagonist were quantitatively confirmed by immunogold studies and immunoblot analysis of the inner medulla. The present results indicate that the distribution and amount of AQP-CD in the CD cells are regulated by vasopressin V2 receptor.